Answer:
19+6x
Step-by-step explanation:
2×2+x+5x+15
4+6x+15
19+6x
Answer:
x = 1
Step-by-step explanation:
the angle 2 is equal to 52, because triangles add up to be 180, and 180 - 76 and divided by two is 52. 52 = 4x + 12. Divide both sides by four, then subtract 12. x = 1
Answer:
x = 5
Step-by-step explanation:
6/18 = x/(20-x)
1/3 = x/(20-x) Multiply both sides by 20-x
(20-x)/3 = x Multiply both sides by 3
20-x = 3x Add x in both sides
20 = 4x Divide both sides by 4
5 = x
Answer:
-3x + 8
Step-by-step explanation:
Simplify. combine like terms (terms with the same amount of variables).
Subtract -2x and x: -2x - x = -3x
-3x + 8 is your answer.
~
Let's solve your system by substitution.
2x−2y=−4;2x+y=11
Rewrite equations:
2x+y=11;2x−2y=−4
Step: Solve2x+y=11for y:
2x+y=11
2x+y+−2x=11+−2x(Add -2x to both sides)
y=−2x+11
Step: Substitute−2x+11foryin2x−2y=−4:
2x−2y=−4
2x−2(−2x+11)=−4
6x−22=−4(Simplify both sides of the equation)
6x−22+22=−4+22(Add 22 to both sides)
6x=18
6x/6 = 18/6
(Divide both sides by 6)
x=3
Step: Substitute3forxiny=−2x+11:
y=−2x+11
y=(−2)(3)+11
y=5(Simplify both sides of the equation)
Answer:
x=3 and y=5